Assessment of Health Literacy Level in Akcadag, Malatya, Turkey - Deniz, Serdar; Oguzoncul, Ayse Ferdane (My University, 2020)
Objective: Health literacy is the knowledge, motivation and abilities of individuals to reach information about health, to understand, interpret andapply this information. In this study, it was aimed to evaluate the health literacy level and the factors affecting the health literacy levels of the population aged 18 and over.Material and Method: Fieldwork was conducted between March and July 2016. The sample size was calculated as 375 among 16.325 males andfemales aged 18 and over from the population registered to seven family medicine units. Turkish version of the European Health Literacy SurveyQuestionnaire and the Newest Vital Sign scale were used in this study.Results: It was determined that 7.2% of the group were illiterate. 50.7% of the participants were male, 78.4% married and 10.9% were in the 65 andover age group. 77.6% of the group whose HLS-EU-Q general health literacy index score average was determined as 27.5±7.41 were in the categoryof inadequate or problematic health literacy. The average score of the NVS scale for the group was 2.60±1.74. In health literacy indices and the NVSscale, the average score of males was higher than the average of females. As the level of education increased, the average scores of the NVS scale andgeneral health literacy index increased.Conclusion: The inclusion of clear information on health in areas frequently used by the community, and the availability of health professionals’effective communication techniques during their training will be effective in increasing the level of health literacy.
Keywords: Halk ve Çevre Sağlığı; Sağlık Politikaları ve Hizmetleri